Alterações fisiológicas e nutricionais durante as fases do desenvolvimento vegetativo e reprodutivo do mamoeiro Golden - Silva, Mariela Mattos da (2009)
The papaya tree is a plant whose reproductive growth is continuous and uninterrupted, and your productivity is influenced by the great variability of responses to the demands of accumulation of assimilates, and photosynthetic characteristics depending on the growth phases and cultivars causing changes in the final quality of the fruit. In order to determine the influence of the vegetative and reproductive development stages on the papaya (Carica papaya L. cv. ‘Golden’) in field conditions, was determined the growth, the macronutrients and dry mass (DM) accumulation, the nitrate reductase activity in the leaves, the concentration of nitrogen in petiole and leaf blade and the chlorophyll a fluorescence. For this study, the plants were initially selected and marked at random in a commercial crop located in Linhares, in the North of Espírito Santo. The growth and the dry mass accumulation happened in a fast way after the transplant of the seedlings to the field, with continuous increase until the beginning of the flowering/fructification of the papaya, where the higher accumulations relative diaries of DM happen. In the reproductive phase the picks of diaries relative accumulation of nutrients happened between 120 and 160 DAP. The development stages influenced the order of nutrient accumulation. N, K and Ca were the most accumulated nutrients during the vegetative stage and with the beginning of the reproductive stage, K became the most accumulated nutrient in the papaya plants. Although it has been accumulated in smaller amounts S was the nutrient more exported to the reproductive organs. The nitrate reductase activity presented expressive reduction with the beginning of the reproductive period, showing the influence of the plant stage development on the metabolism of assimilation of N. Only the N concentrations the petiole presented reductions in function of the days after planting, showing correlation between activity of the enzyme and the nutrient concentration the leaf. The results corroborated the use of the petiole as the best part of the leaf to indicate the “status” of N in papaya plants. The photochemical response of the plants, measured by the chlorophyll a x fluorescence, showed higher values in the vegetative phase, mainly observed in the basic parameters. Moreover, among the parameters OJIP, the flux of photons absorbed by RC (ABS/RC), the dissipation of radiant energy by active RC (DI0/RC), the performance index (PI) and the density of active RCs of FSII (RC/CS0), indicated stress caused by the transplanting of the plants to the field and for the beginning of the reproductive stage. These results show the efficiency of this technique for detecting changes due abiotic factors, as observed in seedlings transplanting in the field, as well as indicated the changes occurred in the beginning of the reproductive phase, wich may have acted as a isolated factor or combined with other environment stresses that the plants are subjected.